Irrigation and drainage system in Hit and Al-Qaim districts and their relationship to the growth of pests and bushes - Al-Ani, Kamal Salih Koskouz; Awad, Sana Rashid (Al-Adab Journal, 2021)
The research dealt with the irrigation and drainage systems in the districts of Hit and Al-Qaim, and the research included the types of the main irrigation systems in the study area and the calculation of the irrigated areas in each system in the two districts, as well as the drainage system in the region as well, the lengths and types of trocars, and the relationship of the irrigation and drainage systems to the growth and reproduction of pests and jungles in the study area The research found that the most common type of irrigation system contributing to the spread of pests and jungles is the intermediary irrigation system, and the least contributing to the spread of pests and jungles is the drip irrigation system, as for the drainage system in the region, it works on the spread of pests and jungles in a clear way and is a focus for spreading them in the neighboring farmland.